The role of visualization in understanding data - Domik, Gitta (New Results and New Trends in Computer Science)

Incremental Design of Conceptual Database Schemata with CADDY - Löhr-Richter, Perdita; Engels, Gregor

Visualization in the Analysis Cycle of Observational Data, in Analyzing and Modeling Data and Knowledge - Domik, Gitta; Mickus, KD (Proceedings of the 15th Annual Conference of the "Gesellschaft für Klassifikation e.V." University of Salzburg)

Contract-Oriented System Design and Specification - Müller, Wolfgang (Proceedings of the Workshop on Practical Computer Based Systems Engineering - its Scope and Methods)

Validation of EXPRESS Models Using Prolog - Lehrenfeld, Georg; Müller, Wolfgang (Proceedings of the 1st EXPRESS User's Group Conference)

Approximation of convex polygons - Alt, Helmut; Blömer, Johannes; Wagener, Hubert (Automata, Languages and Programming)

Formal Semantics of an Entity-Relationship Query Language - Hohenstein, Uwe; Engels, Gregor (Proceedings of the 9th International Conference on Entity-Relationship Approach (ER 90), Lausanne, Switzerland)

Elementary Actions on an Extended Entity-Relationship Database - Engels, Gregor (Proceedings of the workshop on Graph Grammars and Their Application to Computer Science (1990), Bremen (Germany))
Semantic data models have been widely studied for the conceptual specification of databases. However, most of these data models are restricted to the description of the static structure of a database. They do not provide means to specify the dynamic behaviour of a database. This paper sketches a language for the specification of actions on databases which have been specified by an Extended Entity-Relationship (EER) schema. These actions are based on so-called elementary actions, which are automatically be derived from the EER schema. So, it can always be guaranteed that these schema dependent elementary actions preserve all inherent integrity constraints. The semantics of the elementary actions is given in two steps: First, it is shown how the semantics of a database schema, i.e., a current database state, can be represented by an attributed graph. Then, the semantics of elementary actions is given by programmed graph replacements.

A new universal class of hash functions and dynamic hashing in real time - Dietzfelbinger, Martin; Meyer auf der Heide, Friedhelm (Automata, Languages and Programming)

Dynamic hashing strategies - Meyer auf der Heide, Friedhelm (Lecture Notes in Computer Science)

On the complexity of genuinely polynomial computation - Karpinski, Marek; Meyer auf der Heide, Friedhelm (Lecture Notes in Computer Science)

How to distribute a dictionary in a complete network - Dietzfelbinger, M.; Meyer auf der Heide, Friedhelm (Proceedings of the twenty-second annual ACM symposium on Theory of computing - STOC '90)

Not all keys can be hashed in constant time - Gil, J.; Meyer auf der Heide, Friedhelm; Wigderson, A. (Proceedings of the twenty-second annual ACM symposium on Theory of computing - STOC '90)

Das Heinz Nixdorf-Institut der Universität-GH Paderborn - Meyer auf der Heide, Friedhelm (Informatik Spektrum)

IRAS On-Line Catalogs at CASA - Domik, Gitta; Brugel, E.W.; Stencel, R.E. (Proceedings of the 176th meeting of the American Astronomical Society)

Applications of IRAS Preprocessing at the Workstation - Domik, Gitta; Brugel, EW; Stencel, RE; Vasudevan, S; Pang, J (Bulletin of the American Astronomical Society)

Workstation-based preprocessing of IRAS sky-flux images - Domik, Gitta; Brugel, Edward W; Stencel, Robert E; Pang, Jinzhong; Vasudevan, Subramanian (Publications of the Astronomical Society of the Pacific)

A case study: Multi-sensor data analysis of hh objects via star: A scientific toolkit for astrophysical research - Mickus, KD; Brugel, EW; Domik, Gitta; Ayres, TR (Bulletin of the American Astronomical Society)

Star-a scientific toolkit for astrophysical research - Mickus, KD; Domik, Gitta; Brugel, EW; Ayres, TR (Bulletin of the American Astronomical Society)

Projections of vector addition system reachability sets are semilinear - Kleine Büning, Hans; Lettmann, Theodor; Mayr, Ernst W. (Theoretical Computer Science)

Konzepte einer Software-Architektur-Beschreibungssprache - Ebert, Jürgen; Engels, Gregor (Software-Entwicklung: Konzepte, Erfahrungen, Perspektiven, Fachtagung, 1989, Marburg (Germany))

CADDY-O: Syntaxgestütztes, graphisches Entwerfen konzeptioneller Datenbankschemata - Engels, Gregor (Tagungsband GI-Fachtagung "Interaktive Schnittstellen für Informationssysteme", TU Clausthal, Notizen zu Interaktive Systeme)

CADDY: Computer-Aided Design of Non-Standard Databases - Engels, Gregor; Hohenstein, Uwe; Hülsmann, Klaus; Löhr-Richter, Perdita; Ehrich, Hans-Dietrich (Proceedings of the International Conference on System Development Environments & Factories, Berlin, Germany)

Benutzerschnittstelle und Architektur der integrierten Datenbankentwurfsumgebung CADDY (Kurzfassung) - Engels, Gregor

Programmentwicklungsumgebungen: Konzepte und Realisierung - Engels, Gregor; Schäfer, Wilhelm

On computations with integer division - Just, Bettina; Meyer auf der Heide, Friedhelm; Wigderson, Avi (RAIRO - Theoretical Informatics and Applications)

An optimal parallel dictionary - Dietzfelbinger, M.; Meyer auf der Heide, Friedhelm (Proceedings of the first annual ACM symposium on Parallel algorithms and architectures - SPAA '89)

On genuinely time bounded computations - Meyer auf der Heide, Friedhelm (STACS 89)

Time-optimal simulations of networks by universal parallel computers - Meyer auf der Heide, Friedhelm; Wanka, Rolf (STACS 89)

Computing minimum spanning forests on 1- and 2-dimensional processor arrays - Meyer auf der Heide, Friedhelm (STACS 89)

ODICE: Object-Oriented Hardware Description in CAD Environment - Rammig, Franz Josef; Müller, Wolfgang (Proc. of the Ninth IFIP Symposium on CHDLs and their Application)

Perspektiven für die Logikprogrammierung - Kleine Büning, Hans; Lettmann, Theodor (Workshop Wissensrepräsentation in Expertensystemen)

A Highly Integrated Tool Set for Program Development Support - Engels, Gregor; Janning, Thorsten; Schäfer, Wilhelm (Proceedings of the conference on ACM SIGSMALL/PC symposium on ACTES (SIGSMALL 1988), Cannes (France))
This paper describes the design of the integrated user interface of the software development environment IPSEN (Integrated Programming Support Environment). We explain the characteristic features of the IPSEN user interface, namely the structured layout of the screen, the command-driven tool activation, and especially the highly integrated use of the IPSEN tool set. We demonstrate those features by taking a sample set of tools of the IPSEN environment. That tool set supports all the programming-in-the-small activities within IPSEN. Finally, we sketch the realization of two prototypes running on an IBM-AT and a net of SUN workstations.

Konzeption einer integrierten Datenbank-Entwurfsumgebung - Engels, Gregor; Hohenstein, Uwe; Neugebauer, Leonore; Saake, Gunter; Ehrich, Hans-Dietrich (Proceedings of DBTA/SI Data Dictionaries und Entwicklungswerkzeuge für Datenbank-Anwendungen, Zürich, Switzerland)

Auf dem Weg zu einer integrierten Datenbank-Entwurfsumgebung - Engels, Gregor; Hohenstein, Uwe; Saake, Gunter; Ehrich, Hans-Dietrich (Proceedings of the GI-Workshop on "Sprachspezifische Programmierumgebungen")

Ein Konzept zur Beschreibung von Software-Architekturen - Ebert, Jürgen; Engels, Gregor

Die Benutzerschnittstelle einer integrierten Modula-2 Programmentwicklungsumgebung - Engels, Gregor; Janning, Thorsten; Schäfer, Wilhelm (Proceedings of GI-Workshop Sprachspezifische Programmierumgebungen, Darmstadt, Germany)

On the limits of computations with the floor function - Babai, László; Just, Bettina; Meyer auf der Heide, Friedhelm (Information and Computation)

Fast algorithms for N-dimensional restrictions of hard problems - Meyer auf der Heide, Friedhelm (Journal of the ACM (JACM))

A tradeoff between search and update time for the implicit dictionary problem - Borodin, Allan; Fich, Faith E.; Meyer auf der Heide, Friedhelm; Upfal, Eli; Wigderson, Avi (Theoretical Computer Science)

Dynamic perfect hashing: upper and lower bounds - Dietzfelbinger, M.; Karlin, A.; Mehlhorn, K.; Meyer auf der Heide, Friedhelm; Rohnert, H.; Tarjan, R.E. ([Proceedings 1988] 29th Annual Symposium on Foundations of Computer Science)

On computations with integer division - Just, Bettina; Mathematik, Fb; Meyer auf der Heide, Friedhelm; Informatik, Fb; Wigderson, Avi (STACS 88)

Upper and lower bounds for the dictionary problem - Dietzfelbinger, M.; Mehlhorn, K.; Meyer auf der Heide, Friedhelm; Rohnert, H. (SWAT 88)

Enhancement Techniques in Digital Image Processing - Domik, Gitta (Proceedings of the Computer Science Symposium)

A multi-spectral analysis system using large databases. - Brugel, Edward W; Domik, Gitta; Voels, Stephen A (European Southern Observatory Conference and Workshop Proceedings)

Dependence of image grey values on topography in SIR-B images - Domik, Gitta; Leberl, Franz; Cimino, J (International Journal of Remote Sensing)

SIR-B stereo-radargrammetry of Australia - Leberl, Franz; Mayr, W; Domik, Gitta; Kobrick, M (International journal of remote sensing)

Representation independent query and update operations on propositional definite Horn formulas - Büning, Hans Kleine; Lettmann, Theodor (Computation Theory and Logic)

Image based SAR product simulation for analysis - Domik, Gitta; Leberl, Franz (ASPRS-ACSM)

A Hybrid Interpreter in a Software Development Environment - Engels, Gregor; Schürr, Andy (Proceedings of the 1st European Software Engineering Conference (ESEC '87), Strasbourg (France))
This paper describes the realization of an execution tool for Modula-2 modules which is part of an integrated tool set in a software development environment termed IPSEN (Incremental Programming Support Environment). In this environment, all software documents, e.g. Modula-2 modules, are manipulated by syntax-directed editors and are represented internally by attributed graphs. The execution of Modula-2 modules is done by two cooperating interpreters. The first one is a graph interpreter which traverses the internal graph from statement to statement. These statements are translated into a low-level, more efficiently executable object code and interpreted by a second interpreter. This concept of a hybrid interpreter allows the realization of an execution tool which offers a lot of runtime support features to the user.

On the Structure of Structure-Oriented Editors for Different Applications - Engels, Gregor; Nagl, Manfred; Schäfer, Wilhelm (Proceedings of the ACM SIGSOFT/SIGPLAN Software Engineering Symposium on Practical Software Development Environments, Palo Alto, USA)

Graph Grammar Engineering: A Software Specification Method - Engels, Gregor; Lewerentz, Claus; Schäfer, Wilhelm (Proceedings of the 3rd International Workshop on Graph-Grammars and Their Application to Computer Science, Warrenton, VA (USA))
Graphs as conceptual data models are accepted and used in a wide range of different problem areas. Giving some examples we outline common aspects for modeling complex structures by graphs. We present a formal frame-work based on graph grammars to specify graph classes and the corresponding graph manipulations. We show that such a specification can be written in a systematic, engineering-like manner. This is achieved by an extension of the known programmed, attributed graph grammars. Node-set operators are introduced to facilitate graph queries. Concepts like abstraction, decomposition, refinement, parameterization, and integration have been adopted from software engineering to yield a comprehensive specification method. This method has successfully been applied to specify the central data structures in a software development environment project

A Time-Space Tradeoff for Element Distinctness - Borodin, A.; Fich, F.; Meyer auf der Heide, Friedhelm; Upfal, E.; Wigderson, A. (SIAM Journal on Computing)

The Complexity of Parallel Sorting - Meyer auf der Heide, Friedhelm; Wigderson, Avi (SIAM Journal on Computing)

Digital Rectification Method for Radar Images Applied on Huge Arrays - Domik, Gitta (Proceedings of the First Int'l. Workshop on Image Rectification Tech. for Spaceborne Synthetic Aperture Radar)

Methods and application of surface shape reconstruction from multiple SAR images - Domik, Gitta (IGARSS'87-International Geoscience and Remote Sensing Symposium)

Methods and accuracy of operational digital image mapping with aircraft SAR - Leberl, Franz; Domik, Gitta; Mercer, Bryan J (1987 ASPRS ACSM Annual Convention)

Classes of first order formulas under various satisfiability definitions - Kleine Büning, H.; Lettmann, Theodor (8th International Conference on Automated Deduction)

Multiple incidence angle SIR-B experiment over Argentina: generation of secondary image products - Domik, Gitta; Leberl, Franz; Cimino, Jobea (IEEE Transactions on Geoscience and Remote Sensing)

Digital terrain mapping with STAR-1 SAR data - Mercer, JB; Lowry, RT; Leberl, Franz; Domik, Gitta (International Geoscience and Remote Sensing Symposium)

Developing tools for digital radar image data evaluation - Domik, Gitta; Leberl, Franz; Raggam, J (Remote sensing for resources development and environmental management; Proceedings of the Seventh International Symposium)

On the Structure of an Incremental and Integrated Software Development Environment - Engels, Gregor; Lewerentz, Claus; Nagl, Manfred; Schäfer, Wilhelm (Proceedings of the 19th Hawaii International Conference on System Sciences, Hawaii, USA)

Experiences with a Hybrid-Interpreter Based on Incremental Compilation Techniques - Engels, Gregor; Sandbrink, Andrea (Proceedings of the Workshop on Compiler Compilers and Incremental Compilation Techniques, Bautzen)

Graphen als zentrale Datenstrukturen in einer Software-Entwicklungsumgebung - Engels, Gregor

Efficient Simulations among Several Models of Parallel Computers - Meyer auf der Heide, Friedhelm (SIAM Journal on Computing)

A tradeoff between search and update time for the implicit dictionary problem - Borodin, Allan; Fich, Faith E.; Meyer auf der Heide, Friedhelm; Upfal, Eli; Wigderson, Avi (Automata, Languages and Programming)

Speeding up random access machines by few processors - Meyer auf der Heide, Friedhelm (STACS 86)

A time-space tradeoff for element distinctness - Borodin, A.; Fich, F.; Meyer auf der Heide, Friedhelm; Upfal, E.; Wigderson, A. (STACS 86)

Radar Stereomapping Techniques and Application to SIR-B Images of Mt. Shasta - Leberl, F.; Domik, Gitta; Raggam, J.; Kobrick, M. (IEEE Transactions on Geoscience and Remote Sensing)

Multiple Incidence Angle SIR-B Expenment Over Argentina: Stereo-Radargrammetrc Analysis - Leberl, F.; Domik, Gitta; Raggam, J.; Cimino, J.; Kobrick, M. (IEEE Transactions on Geoscience and Remote Sensing)

Using secondary image products to aid in understanding and interpretation of radar imagery - Domik, Gitta; Leberl, Franz (IGARSS'86: Remote Sensing: Today's Solutions for Tomorrow's Information Needs)

Radargrammetric Experiments with Space Shuttle SIR-B Imagery - Leberl, Franz; Domik, Gitta; Raggam, J; Cimino, J; Kobrick, M (International archives of photogrammetry and remote sensing= Archives internationales de photogrammétrie et de télédétection= Internationales Archiv der Photogrammetrie und Fernerkundung)

Radar image simulation as a tool to analyze topographic effects on geometry and radiometry of radar imagery - Domik, Gitta (Machine processing of remotely sensed data- Quantifying global process: Models, sensor systems, and analytical methods)

Radargrammetric aspects of SAR data evaluation - Raggam, J; Triebnig, Gerhard; Buchroithner, MF; Domik, Gitta; Leberl, Franz (Thematic Applications of SAR data)

Graph Grammar Engineering: A Method Used for the Development of an Integrated Programming Support Environment - Engels, Gregor; Schäfer, Wilhelm (Proceedings of the International Joint Conference on Theory and Practice of Software Development (TAPSOFT 1985), Berlin (Germany))
We introduce a method to specify the functional behaviour of software tools in an incremental and integrated software development environment. This specification method is based on graph grammars. It is an adequate method to specify the behaviour of all software systems using graphs as internal data structures. We show that a specification can be developed systematically by which the adaptability of the environment is increased towards modification of tools or extension by new tools. Furthermore, guidelines for the implementation can directly be derived from this specification.

The Design of an Adaptive and Portable Programming Support Environment - Engels, Gregor; Schäfer, Wilhelm (Proceedings of the International Computing Symposium, Amsterdam (The Netherlands))

Lower time bounds for integer programming with two variables - Lautemann, Clemens; Meyer auf der Heide, Friedhelm (Information Processing Letters)

Lower bounds for solving linear diophantine equations on random access machines - Meyer auf der Heide, Friedhelm (Journal of the ACM (JACM))

Simulating probabilistic by deterministic algebraic computation trees - Meyer auf der Heide, Friedhelm (Theoretical Computer Science)

The complexity of parallel sorting - Meyer auf der Heide, Friedhelm; Wigderson, Avi (26th Annual Symposium on Foundations of Computer Science (sfcs 1985))

One, two, three . . . infinity: lower bounds for parallel computation - Fich, F E; Meyer auf der Heide, Friedhelm; Ragde, P; Wigderson, A (Proceedings of the seventeenth annual ACM symposium on Theory of computing - STOC '85)

Fast algorithms for n-dimensional restrictions of hard problems - Meyer auf der Heide, Friedhelm (Proceedings of the seventeenth annual ACM symposium on Theory of computing - STOC '85)

Nondeterministic versus probabilistic linear search algorithms - Meyer auf der Heide, Friedhelm (26th Annual Symposium on Foundations of Computer Science (sfcs 1985))

Lower time bounds for solving linear diophantine equations on several parallel computational models - Meyer auf der Heide, Friedhelm (Information and Control)

Mapping with aircraft and satellite radar images - Leberl, FW; Kobrick, M; Domik, Gitta (The Photogrammetric Record)

Towards a SAR system for snow and land ice applications - Rott, H; Domik, Gitta; Mätzler, C; Miller, H (ESA Proceedings of a Workshop on Thematic Applications of SAR DATA p 29-39(SEE N 86-28488 19-42))

Radar Image Simulation and its Application in Image Analysis - Domik, Gitta; Leberl, F.; Kobrick, M. (International archives of photogrammetry and remote sensing)

Rectification of Radar Images Using Stereo- Derived Height Models and Simulations - Domik, Gitta; Leberl, F.; Raggam, J. (XVth Congress of the International Society for Photogrammetry and Remote Sensing)

Evaluation of radar stereo viewability by means of a simulation technique - Domik, Gitta (ESA IGARSS 84: Remote Sensing: From Res. towards Operational Use,)

A Polynomial Linear Search Algorithm forr the n-Dimensional Knapsack Problem - Meyer auf der Heide, Friedhelm (Journal of the ACM (JACM))

On The Limits To Speed Up Parallel Machines By Large Hardware And Unbounded Communication - Meyer auf der Heide, Friedhelm; Reischuk, R. (25th Annual Symposium onFoundations of Computer Science, 1984.)

Efficient simulations among several models of parallel computers (extended abstract) - Meyer auf der Heide, Friedhelm (STACS 84)

Method to Relate Digital SAR Images and Map Information in Mountainous Areas - Domik, Gitta; Kienegger, E. (Proceedings of the World Conference on Remote Sensing)

The SAR-580 experiment on snow and glaciers at the Austrian test site - Rott, H.; Domik, Gitta (Proc. SAR-580 Investigators Workshop)

Differential Rectification of SLR-Images Using Map-Derived and Radar-Generated Digital Elevation Models. - Domik, Gitta; Leberl, Franz; Raggam, Johannes

Analyse von Radarbildern mittels digitaler Hoehenmodelle - Domik, Gitta; Kobrick, M; Leberl, Franz (Bildmessung und luftbildwesen)

Software Specification by Graph Grammars - Nagl, Manfred; Engels, Gregor; Gall, Rupert; Schäfer, Wilhelm (Proceedings of the 2nd International Workshop on Graph-Grammars and Their Application to Computer Science, Osnabrück (Germany))
The following paper demonstrates that programmed sequential graph grammars can be used in a systematic proceeding to specify the changes of high level intermediate data structures arising in a programming support environment, in which all tools work in an incremental and syntax-driven mode. In this paper we lay stress upon the way to get the specification rather than on the result of this process. Therefore, we give here some approach to specification engineering using graph grammars. This approach is influenced by the syntactical definition of the underlying programming language or module concept etc. to be supported but also by the idea of the user interface.

Software Specification Using Graph Grammars - Engels, Gregor; Gall, Rupert; Nagl, Manfred; Schäfer, Wilhelm (Computing)
The following paper,demonstrates that programmed sequential graph grammars can be used in a systematic proceeding to specify tbe changes of high level intermediate data structures arising in a programming support environment, in which all tools work in an incremental and syntax-driven mode. In this paper we lay stress upon the way to get the specification rather than on the result of this process. Therefore, we give here some approach to "specification engineering" using graph grammars. This approach is influenced by the syntactical definition of the underlying language for Programming in the Small, the module concept etc. to be supported on one side but also by the idea of the user interface.

An Operational Semantics for Specifications of Abstract Data Types with Error Handling - Engels, Gregor; Pletat, Udo; Ehrich, Hans-Dietrich (Acta Informatica)
A new approach to an operational treatment of errors and exceptions in specifications of abstract data types is presented. Considering a specification as a term rewriting system, we define an operational semantics and give conditions that are sufficient for its well-definedness (Church-Rosser property). Also, we give conditions that are sufficient for the termination of reduction strategies, respecting the specified error and exception handling.

Efficiency of universal parallel computers - Meyer auf der Heide, Friedhelm (Acta Informatica)